Thermocuring high-temperature-resistant electronic paste and preparation method thereof

Through the use of thermally curing electronic paste with components such as silane, silica sol and glass powder in a specific ratio, the problem of insufficient high temperature resistance of existing electronic paste in extreme application scenarios is solved, and good electrical performance and printing accuracy are maintained under high temperature conditions.

CN120748798APending Publication Date: 2025-10-03NANTONG AIBIO NEW MATERIALS TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511092073.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-08-05
Publication Date
2025-10-03

AI Technical Summary

Technical Problem

Existing electronic pastes lack high temperature resistance in extreme application scenarios, which affects electrical performance.

Method used

By using components such as silane, silica sol, glass powder and filler in a specific ratio and limiting the reaction and mixing process of the compounds, a thermosetting electronic paste with good high temperature resistance and electrical properties is formed.

Benefits of technology

It maintains good electrical properties under high temperature conditions, solves the problems of high dielectric constant and weak bonding force of conventional silica sol, improves the heat resistance and electrical properties of electronic paste, and improves printing accuracy.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005534236200000091
    Figure BDA0005534236200000091
  • Figure BDA0005534236200000101
    Figure BDA0005534236200000101
Patent Text Reader

Abstract

The invention belongs to the technical field of electronic materials, and particularly relates to thermocuring high-temperature-resistant electronic paste and a preparation method thereof.The electronic paste is prepared from, by weight, 35-45 parts of silane A, 1-2.25 parts of silane B, 1-5 parts of silane C, 25-35 parts of silica sol, 0.5-1 part of a pH regulator, 25-35 parts of a solvent A, 1-3 parts of a chain extender, 20-40 parts of a solvent B, 2-5 parts of glass powder and 22-44 parts of filler. The electronic paste prepared by the invention has good high temperature resistance, and can still maintain good electrical properties under a high temperature condition.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of electronic materials, and in particular relates to a heat-curing high-temperature resistant electronic paste and a preparation method thereof. Background Art

[0002] Electronic paste is an electronic functional material that integrates metallurgy, chemical engineering, and electronic technology. Its main technical applications cover high-end electronic manufacturing fields such as photovoltaic cell electrode preparation, printed electronic circuits, high-precision electronic wiring, functional sensor manufacturing, integrated circuit packaging, and special conductive inks. The typical composition system of electronic paste includes a conductive functional phase, an inorganic binder, an organic carrier system (solvents and diluents), and various functional additives. A conductive network structure can be formed through the printing process. During the subsequent high-temperature heat treatment process, the organic carrier components undergo thermal decomposition and volatilization, while the inorganic binder melts to form a glass phase, prompting the conductive particles to sinter on the substrate surface to form a densified functional film layer. The spatial distribution state of the conductive particles and their interfacial contact characteristics are key factors affecting the final film performance, and are directly related to the degree of densification and electrical performance of the conductive film. At present, electronic paste technology still faces many challenges.

[0003] For example, patent CN114023887B discloses a tin oxide electronic paste and its preparation method and application, which includes mixing tin oxide nanoparticles with a metal ion dopant, a solvent, and a binder and performing a dispersion treatment, wherein the molar ratio of the tin oxide nanoparticles to the metal ion dopant is determined according to the desired electrical properties of the tin oxide electronic paste; the binder is used for bonding, forming pores, and dispersing the paste; and the mixture after the dispersion treatment is concentrated to obtain the desired tin oxide electronic paste. A tin oxide film layer is further obtained by coating and sintering, which can be used as a carrier transport layer or buffer layer in optoelectronic devices such as solar cells, light-emitting diodes, and field-effect transistors. This invention can adjust the semiconductor properties of the tin oxide film layer by performing a doping treatment during the paste preparation process to achieve improved device performance. In addition, the process is simple, the conditions are easy to control, and it can be prepared in batches, which has good application prospects.

[0004] Patent CN114023511B discloses a method for preparing a high-temperature electronic paste based on an organic phosphate salt. The invention utilizes n-hexyl-3-methylimidazolium hexafluorophosphate to surface-modify the conductive phase powder, improving dispersibility and bonding strength. The high-temperature electronic paste comprises the following components, by weight: 7-12 parts of a novel slurry carrier, 78-90 parts of conductive powders of varying particle sizes, and 3-5 parts of a glass phase. By utilizing n-hexyl-3-methylimidazolium hexafluorophosphate to bind to the surface of the conductive phase, the invention achieves uniform distribution of the slurry particles. This not only enhances bonding strength between the conductive particles and forms a dense film, but also improves the paste's conductivity and performance.

[0005] Although the above patents have improved the high-temperature resistance of electronic pastes to a certain extent, the high-temperature resistance still needs to be further improved in the face of some extreme application scenarios. Therefore, there is an urgent need for an electronic paste with good high-temperature resistance on the market. Summary of the Invention

[0006] In order to overcome the above-mentioned deficiencies of the prior art, the present invention provides a thermosetting high-temperature resistant electronic paste and a preparation method thereof. The electronic paste prepared by the present invention has good high-temperature resistance and can still maintain good electrical properties under high-temperature conditions.

[0007] In order to achieve the above object, the technical solution adopted by the present invention is:

[0008] A first aspect of the present invention provides a thermosetting, high-temperature resistant electronic paste, which comprises the following raw materials, in parts by weight: 35-45 parts of silane A, 1-2.25 parts of silane B, 1-5 parts of silane C, 25-35 parts of silica sol, 0.5-1 part of a pH adjuster, 25-35 parts of a solvent A, 1-3 parts of a chain extender, 20-40 parts of a solvent B, 2-5 parts of glass powder, and 22-44 parts of a filler.

[0009] In some embodiments, the silane A is at least one of methyltrimethoxysilane and methyltriethoxysilane.

[0010] In some embodiments, the silane B is at least one of dimethyldimethoxysilane and dimethyldiethoxysilane.

[0011] In some embodiments, the silane C is any one or more of γ-glycidyloxypropyltrimethoxysilane, γ-glycidyloxypropyltriethoxysilane, propyltrimethoxysilane, butyltrimethoxysilane, octyltrimethoxysilane, phenyltrimethoxysilane, phenyltriethoxysilane, γ-methacryloxypropyltrimethoxysilane, γ-methacryloxypropyltriethoxysilane, perfluorodecyltrimethoxysilane, perfluorodecyltriethoxysilane, perfluorooctyltrimethoxysilane, and perfluorooctyltriethoxysilane.

[0012] Preferably, the silane C is γ-glycidyloxypropyltrimethoxysilane.

[0013] In some embodiments, the method for preparing the silica sol comprises the following steps:

[0014] (1) 1-vinylimidazole and chloromethyltrimethylsilane were added to a reaction vessel, heated to 115-125° C., reacted for 23-25 ​​hours, washed, distilled, and dried to obtain compound 1;

[0015] (2) Under nitrogen protection, compound 1 obtained in step (1), vinyltriethoxysilane, and an initiator were added to acetone, reacted at 65-75° C. for 1-2 h, washed, and dried to obtain compound 2;

[0016] (3) Compound 2 obtained in step (2) and sodium tetrafluoroborate were added to anhydrous ethanol, heated to 75-85°C for reaction for 23-25 ​​hours, washed, and dried to obtain compound 3;

[0017] (4) Tetraethyl orthosilicate was added to ethanol and stirred at 35-45° C. for 5-10 min, and then a mixture of hydrochloric acid and water was added and reacted for 3-4 h. Then, compound 3 obtained in step (3) was added and the reaction was continued for 1-2 h to obtain silica sol.

[0018] Conventional silica sol has a high dielectric constant, and adding it to electronic paste may increase dielectric loss, affecting the signal transmission efficiency of high-frequency circuits. In addition, it has a weak binding force with metal particles, which easily forms interfacial voids after sintering, increasing contact resistance and causing the electrical performance of electronic components to deteriorate. The present invention reacts 1-vinylimidazole with chloromethyltrimethylsilane to obtain compound 1, which is then polymerized with vinyltriethoxysilane to obtain compound 2, which is then anion-exchanged with sodium tetrafluoroborate to obtain compound 3. Compound 3 is then reacted with tetraethyl orthosilicate to prepare silica sol. The resulting silica sol increases the interfacial binding force with metal ions, reduces the loss of electrical performance, and also improves high temperature resistance to a certain extent. The possible reason is that the addition of uniformly distributed nitrogen atoms to the silica sol increases the interfacial force with metal particles; the weak coordination ability of tetrafluoroborate can reduce the agglomeration of metal particles and improve the dispersibility of the slurry. As a weak acid radical, tetrafluoroborate can adjust the pH value of the slurry and inhibit the oxidation of certain metal particles. At the same time, tetrafluoroborate can participate in the formation of conductive paths, reduce contact resistance, and improve electrical performance.

[0019] In some embodiments, the mass ratio of the 1-vinylimidazole to chloromethyltrimethylsilane is 1:(1.3-1.6).

[0020] In some embodiments, the mass ratio of compound 1 to vinyltriethoxysilane in step (2) is (0.4-0.7):1.

[0021] In some embodiments, the mass ratio of compound 2 to sodium tetrafluoroborate in step (3) is 1:

[0022] (0.27-0.41).

[0023] In some embodiments, the mass ratio of tetraethyl orthosilicate to compound 3 in step (4) is 1:(0.1-0.4).

[0024] The present invention defines the ratio of 1-vinylimidazole and chloromethyltrimethylsilane to form a silane ionic liquid, namely compound 1, and then polymerizes compound 1 with vinyltriethoxysilane. The ratio of the two is defined so that silane and chloride ions are uniformly distributed on the alkane side chain, which is conducive to the reaction of compound 2 with sodium tetrafluoroborate. At the same time, the ratio of compound 2 to sodium tetrafluoroborate is defined so that chloride ions and tetrafluoroborate undergo ion exchange, thereby enhancing the electrical properties and heat resistance of the electronic paste. In addition, by defining the mass ratio of tetraethyl orthosilicate to compound 3, the electrical properties and heat resistance of the electronic paste are improved while not corroding the substrate.

[0025] In some embodiments, the pH adjuster is any one or more of formic acid, acetic acid, and hydrochloric acid.

[0026] Preferably, the pH adjuster is acetic acid.

[0027] In some embodiments, the solvent A is any one or more of methanol, ethanol, and isopropanol.

[0028] Preferably, the solvent A is a combination of ethanol and isopropanol, and the mass ratio of the two is 1:(2-4).

[0029] In some embodiments, the solvent B is any one or more of butyl carbitol acetate, propylene glycol methyl ether acetate, ethylene glycol butyl ether, and dimethyl nylonate.

[0030] Preferably, the solvent B is a composition of propylene glycol methyl ether acetate and ethylene glycol butyl ether, and the mass ratio of the two is 1:(1-2).

[0031] In some embodiments, the chain extender is a low-viscosity linear hydroxy silicone oil.

[0032] Preferably, the viscosity of the low-viscosity linear hydroxy silicone oil at 25° C. is 50-100 mPa·s.

[0033] The present invention uses low-viscosity linear hydroxy silicone oil as a chain extender, which reacts with silane during high-temperature sintering to form a three-dimensional network structure, thereby improving the temperature resistance of the cured film. In addition, it has a certain dilution effect that can effectively reduce the viscosity of the electronic paste, avoid problems such as screen blocking and wire drawing during screen printing, and improve printing accuracy.

[0034] In some embodiments, the filler is a combination of a conductive filler and a reinforcing filler.

[0035] Preferably, the filler is a composition of a conductive filler and a reinforcing filler, and the mass ratio of the conductive filler and the reinforcing filler is (9-11):1.

[0036] Further preferably, the conductive filler is conductive ATO or silver powder; and the reinforcing filler is conductive potassium titanate whisker or conductive mica powder.

[0037] In some embodiments, the glass frit is a low-melting-point glass frit.

[0038] A second aspect of the present invention provides a method for preparing a heat-curable high-temperature resistant electronic paste, comprising the following steps:

[0039] S1. Add silane A, silane B, silane C, and solvent A to the first reaction kettle and stir at 50-60° C. for 5-10 minutes to obtain solution A;

[0040] S2. Add the pH regulator and silica sol into the second reaction kettle and stir for 5-10 minutes to obtain solution B;

[0041] S3, adding glass powder, filler and part of solvent B into a grinder, and grinding until the average particle size is less than 40 μm to obtain slurry A;

[0042] S4. Add solution A obtained in step S1 to solution B obtained in step S2, heat the mixture to 30-50° C. and react for 2-3 hours. Then heat the mixture to 70-75° C. and distill the mixture at an absolute pressure of 280-320 mbar for 2.5-3.5 hours. Then, add the remaining solvent B and chain extender, continue heating the mixture to 80-90° C. and distill the mixture at an absolute pressure of 480-520 mbar for 1-2 hours. Then, add slurry A obtained in step S3, and continue stirring for 10-20 minutes to obtain a thermosetting high-temperature resistant electronic paste.

[0043] Compared with the prior art, the present invention has the following beneficial effects:

[0044] 1. The present invention obtains a heat-curing electronic paste with good high temperature resistance and electrical properties by using different types of silane, silica sol, glass powder, filler and other additives.

[0045] 2. The silica sol prepared by the present invention is used in electronic pastes, which increases the interfacial bonding force with metal ions and reduces the loss of electrical properties. It solves the problem that conventional silica sols easily form interfacial voids after sintering, resulting in a decrease in the electrical properties of electronic components. It also solves the problem that conventional silica sols have a high dielectric constant and the electrical properties decrease when added to electronic pastes. In addition, tetrafluoroborate, as a weak acid radical, can adjust the pH value of the paste and inhibit the oxidation of certain metal particles. At the same time, tetrafluoroborate can participate in the formation of conductive paths to reduce contact resistance, thereby further improving the electrical properties.

[0046] 3. The present invention preferably uses low-viscosity linear hydroxy silicone oil as a chain extender. On the one hand, it reacts with silane during high-temperature sintering to form a three-dimensional network structure, thereby improving the temperature resistance of the cured film. On the other hand, it has a certain dilution effect and can effectively reduce the viscosity of the electronic paste, thereby solving problems such as screen blocking and wire drawing during screen printing and improving printing accuracy. DETAILED DESCRIPTION

[0047] The present invention will be described below in conjunction with specific embodiments. It should be noted that the following examples and comparative examples are intended only to illustrate the present invention and are not intended to limit the present invention. Other combinations and various modifications within the scope of the present invention may be made without departing from the spirit or scope of the present invention.

[0048] In order to facilitate those skilled in the art to implement the present invention, some of the raw materials and manufacturers of the examples and comparative examples are described as follows: The low viscosity linear hydroxy silicone oil model is FINISH WS 62CN, with a viscosity of 60 mPa·s (25°C), was purchased from Nanjing Chuhai New Materials Technology Co., Ltd.; hydroxy silicone oil IOTA 8861 with a viscosity of 200 mPa·s (25°C) was purchased from Anhui Aiyota Silicone Oil Co., Ltd.; conductive ATO with a particle size of 5000 mesh was purchased from Qinghe Chaotai Metal Materials Co., Ltd.; conductive mica powder with a particle size of 1000 mesh was purchased from Lingshou Malin Mineral Products Processing Plant; electronic grade low-melting point glass powder with a softening temperature of 350°C was purchased from Foshan Jinggu Materials Technology Co., Ltd.

[0049] The compounds and related reagents used in other examples and comparative examples can all be purchased from the market.

[0050] Preparation Example 1

[0051] The preparation method of silica sol-1 comprises the following steps:

[0052] (1) 10 g of 1-vinylimidazole and 15 g of chloromethyltrimethylsilane were added to a reaction vessel, heated to 120° C. and reacted for 24 h, washed, distilled, and dried to obtain compound 1;

[0053] (2) Under nitrogen protection, 5 g of compound 1 obtained in step (1), 10 g of vinyltriethoxysilane, and 0.1 g of azobisisobutyronitrile were added to 100 ml of anhydrous acetone, reacted at 70° C. for 1.5 h, washed, and dried to obtain compound 2;

[0054] (3) 10 g of compound 2 obtained in step (2) and 3.5 g of sodium tetrafluoroborate were added to 50 ml of anhydrous ethanol, heated to 80° C., reacted for 24 h, washed, and dried to obtain compound 3;

[0055] (4) 10 g of tetraethyl orthosilicate was added to 60 g of anhydrous ethanol and stirred at 40° C. for 8 min. Then, a mixture of 0.01 ml of 37 wt % hydrochloric acid and 2 ml of water was added and the mixture was reacted for 3.5 h. Then, 3 g of compound 3 obtained in step (3) was added and the reaction was continued for 1.5 h to obtain silica sol-1.

[0056] Preparation Example 2

[0057] The preparation method of silica sol-2 is the same as that of Preparation Example 1, except that the amount of compound 1 added in step (2) is 9 g.

[0058] Preparation Example 3

[0059] The preparation method of silica sol-3 is the same as that of Preparation Example 1, except that the amount of compound 3 added in step (4) is 6 g.

[0060] Preparation Example 4

[0061] The preparation method of silica sol-4 includes the following steps: adding 10g of tetraethyl orthosilicate to 60g of anhydrous ethanol and stirring at 40°C for 8 minutes, then adding 0.01ml of a mixture of 37wt% hydrochloric acid and 2ml of water, and reacting for 3.5h to obtain silica sol-4.

[0062] Example 1

[0063] A thermosetting, high-temperature-resistant electronic paste comprises the following raw materials, measured in parts by weight: 40 parts of methyltrimethoxysilane, 1.5 parts of dimethyldimethoxysilane, 3 parts of γ-glycidyloxypropyltrimethoxysilane, 30 parts of silica sol-1, 0.8 parts of acetic acid, 30 parts of solvent A, 2 parts of a chain extender, 30 parts of solvent B, 4 parts of electronic-grade low-melting-point glass powder, and 33 parts of a filler.

[0064] Among them, solvent A is a combination of ethanol and isopropanol, and the mass ratio of the two is 1:3; solvent B is a combination of propylene glycol methyl ether acetate and ethylene glycol butyl ether, and the mass ratio of the two is 1:1.5; the chain extender is a low-viscosity linear hydroxy silicone oil with a viscosity of 60mPa·s (25°C); the filler is a combination of conductive ATO and conductive mica powder, and the mass ratio of the two is 10:1.

[0065] The preparation method of the heat-curable high-temperature resistant electronic paste in this embodiment includes the following steps:

[0066] S1, adding methyltrimethoxysilane, dimethyldimethoxysilane, γ-glycidyloxypropyltrimethoxysilane, and solvent A into a first reaction kettle and stirring at 55° C. for 8 minutes to obtain solution A;

[0067] S2, adding acetic acid and silica sol-1 into the second reaction kettle and stirring for 8 minutes to obtain solution B;

[0068] S3, adding electronic grade low melting point glass powder, filler and two-thirds of solvent B into a grinder, and grinding to an average particle size of 35 μm to obtain slurry A;

[0069] S4. Add solution A obtained in step S1 to solution B obtained in step S2, heat to 40°C and react for 2.5 hours, then heat to 73°C and distill at an absolute pressure of 300 mbar for 3 hours, then add the remaining solvent B and chain extender, continue to heat to 85°C, distill at an absolute pressure of 500 mbar for 1.5 hours, then add slurry A obtained in step S3, continue stirring for 15 minutes to obtain a thermosetting high-temperature resistant electronic paste.

[0070] Example 2

[0071] A thermosetting, high-temperature-resistant electronic paste comprises the following raw materials, measured in parts by weight: 35 parts of methyltrimethoxysilane, 1 part of dimethyldimethoxysilane, 1 part of γ-glycidyloxypropyltrimethoxysilane, 25 parts of silica sol-1, 0.5 parts of acetic acid, 25 parts of solvent A, 1 part of chain extender, 20 parts of solvent B, 2 parts of electronic-grade low-melting-point glass powder, and 22 parts of filler.

[0072] Among them, solvent A is a combination of ethanol and isopropanol, and the mass ratio of the two is 1:3; solvent B is a combination of propylene glycol methyl ether acetate and ethylene glycol butyl ether, and the mass ratio of the two is 1:1.5; the chain extender is a low-viscosity linear hydroxy silicone oil with a viscosity of 60mPa·s (25°C); the filler is a combination of conductive ATO and conductive mica powder, and the mass ratio of the two is 10:1.

[0073] The preparation method of the heat-curable high-temperature resistant electronic paste in this embodiment includes the following steps:

[0074] S1, adding methyltrimethoxysilane, dimethyldimethoxysilane, γ-glycidyloxypropyltrimethoxysilane, and solvent A into a first reaction kettle and stirring at 50° C. for 10 min to obtain solution A;

[0075] S2, adding acetic acid and silica sol-1 into the second reaction kettle and stirring for 5 minutes to obtain solution B;

[0076] S3, adding electronic grade low melting point glass powder, filler and two-thirds of solvent B into a grinder, and grinding to an average particle size of 35 μm to obtain slurry A;

[0077] S4. Add solution A obtained in step S1 to solution B obtained in step S2, heat to 30°C and react for 3 hours, then heat to 70°C and distill at an absolute pressure of 280 mbar for 3.5 hours, then add the remaining solvent B and chain extender, continue to heat to 80°C, distill at an absolute pressure of 480 mbar for 2 hours, then add slurry A obtained in step S3, and continue stirring for 10 minutes to obtain a thermosetting high-temperature resistant electronic paste.

[0078] Example 3

[0079] A thermosetting, high-temperature-resistant electronic paste comprises the following raw materials, measured in parts by weight: 45 parts of methyltrimethoxysilane, 2.25 parts of dimethyldimethoxysilane, 5 parts of γ-glycidyloxypropyltrimethoxysilane, 35 parts of silica sol-1, 1 part of acetic acid, 35 parts of solvent A, 3 parts of chain extender, 40 parts of solvent B, 5 parts of electronic-grade low-melting-point glass powder, and 44 parts of filler.

[0080] Among them, solvent A is a combination of ethanol and isopropanol, and the mass ratio of the two is 1:3; solvent B is a combination of propylene glycol methyl ether acetate and ethylene glycol butyl ether, and the mass ratio of the two is 1:1.5; the chain extender is a low-viscosity linear hydroxy silicone oil with a viscosity of 60mPa·s (25°C); the filler is a combination of conductive ATO and conductive mica powder, and the mass ratio of the two is 10:1.

[0081] The preparation method of the heat-curable high-temperature resistant electronic paste in this embodiment includes the following steps:

[0082] S1, adding methyltrimethoxysilane, dimethyldimethoxysilane, γ-glycidyloxypropyltrimethoxysilane, and solvent A into a first reaction kettle and stirring at 60° C. for 5 minutes to obtain solution A;

[0083] S2, adding acetic acid and silica sol-1 into the second reaction kettle and stirring for 10 minutes to obtain solution B;

[0084] S3, adding electronic grade low melting point glass powder, filler and two-thirds of solvent B into a grinder, and grinding to an average particle size of 35 μm to obtain slurry A;

[0085] S4. Add solution A obtained in step S1 to solution B obtained in step S2, heat to 50°C and react for 2 hours, then heat to 75°C and distill at an absolute pressure of 320 mbar for 2.5 hours, then add the remaining solvent B and chain extender, continue to heat to 90°C, distill at an absolute pressure of 520 mbar for 1 hour, then add slurry A obtained in step S3, and continue stirring for 20 minutes to obtain a thermosetting high-temperature resistant electronic paste.

[0086] Example 4

[0087] A heat-curing high-temperature resistant electronic paste and a preparation method thereof. The specific implementation method is the same as that of Example 1, except that an equal amount of silica sol-1 is replaced by silica sol-2.

[0088] Example 5

[0089] A heat-curing high-temperature resistant electronic paste and a preparation method thereof. The specific implementation method is the same as that of Example 1, except that an equal amount of silica sol-1 is replaced by silica sol-3.

[0090] Example 6

[0091] A heat-curing high-temperature resistant electronic paste and a preparation method thereof. The specific implementation method is the same as that of Example 1, except that an equal amount of silica sol-1 is replaced by silica sol-4.

[0092] Example 7

[0093] A heat-curing high-temperature resistant electronic paste and a preparation method thereof. The specific implementation method is the same as that of Example 1, except that the chain extender is replaced by an equal amount of hydroxy silicone oil IOTA 8861 with a viscosity of 200 mPa·s (25°C).

[0094] Performance Testing

[0095] The electronic paste prepared in each embodiment was printed on a ceramic substrate by screen printing. The thickness of the printed film was 30 μm. The printed film was then placed in a constant temperature drying oven at 80°C for 15 minutes and then heated to 120°C for 30 minutes to form a circuit board. The resistivity of the circuit board was tested at 30°C, 500°C, and 900°C using the four-probe method according to ASTM F1711-96 (2016).

[0096] The test results are shown in Table 1.

[0097] Table 1

[0098]

[0099]

[0100] By comparing the experimental data of Examples 1-3 in Table 1, it can be seen that the electronic paste has good temperature resistance and conductivity; by comparing Example 4 with Example 1, it can be seen that the change in the ratio of compound 1 to vinyltriethoxysilane may lead to excessive nitrogen atom content in the silica sol, affecting the fusion between filler particles, resulting in insufficient sintering and decreased temperature resistance; by comparing Example 5 with Example 1, it can be seen that the change in the ratio of tetraethyl orthosilicate to compound 3 may lead to the generation of insulating fluorides during the sintering process, affecting the connectivity of the conductive network and decreasing the electrical performance; by comparing Example 6 with Example 1, it can be seen that the use of conventional silica sol reduces both the temperature resistance and conductivity; by comparing Example 7 with Example 1, it can be seen that the change in the viscosity of the chain extender may lead to poor fluidity of the slurry, uneven local cross-linking, and decreased temperature resistance.

[0101] The above description is merely a preferred embodiment of the present invention and does not constitute any form of limitation to the present invention. Although the present invention has been disclosed as a preferred embodiment, it is not intended to limit the present invention. Any technician familiar with the present profession can make some changes or modifications to equivalent embodiments of equivalent changes using the technical contents disclosed above without departing from the scope of the technical solution of the present invention. However, any simple modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution of the present invention.

Claims

1. A heat-curing high-temperature resistant electronic paste, characterized in that: The invention comprises the following raw materials in parts by weight: 35-45 parts of silane A, 1-2.25 parts of silane B, 1-5 parts of silane C, 25-35 parts of silica sol, 0.5-1 parts of pH adjuster, 25-35 parts of solvent A, 1-3 parts of chain extender, 20-40 parts of solvent B, 2-5 parts of glass powder, and 22-44 parts of filler.

2. The heat-curing high-temperature resistant electronic paste according to claim 1, characterized in that: The silane A is at least one of methyltrimethoxysilane and methyltriethoxysilane.

3. The heat-curable high-temperature resistant electronic paste according to claim 1, characterized in that: The silane B is at least one of dimethyldimethoxysilane and dimethyldiethoxysilane.

4. The heat-curable high-temperature resistant electronic paste according to claim 1, characterized in that: The silane C is any one or more of γ-glycidyloxypropyltrimethoxysilane, γ-glycidyloxypropyltriethoxysilane, propyltrimethoxysilane, butyltrimethoxysilane, octyltrimethoxysilane, phenyltrimethoxysilane, phenyltriethoxysilane, γ-methacryloxypropyltrimethoxysilane, γ-methacryloxypropyltriethoxysilane, perfluorodecyltrimethoxysilane, perfluorodecyltriethoxysilane, perfluorooctyltrimethoxysilane, and perfluorooctyltriethoxysilane.

5. The heat-curable high-temperature resistant electronic paste according to claim 1, characterized in that: The preparation method of the silica sol comprises the following steps: (1) 1-vinylimidazole and chloromethyltrimethylsilane were added to a reaction vessel, heated to 115-125°C, reacted for 23-25 ​​hours, washed, distilled, and dried to obtain compound 1; (2) Under nitrogen protection, compound 1 obtained in step (1), vinyltriethoxysilane, and an initiator were added to acetone, reacted at 65-75° C. for 1-2 h, washed, and dried to obtain compound 2; (3) Compound 2 obtained in step (2) and sodium tetrafluoroborate were added to anhydrous ethanol, heated to 75-85°C for reaction for 23-25 ​​hours, washed, and dried to obtain compound 3; (4) Tetraethyl orthosilicate was added to ethanol and stirred at 35-45° C. for 5-10 min, and then a mixture of hydrochloric acid and water was added and reacted for 3-4 h. Then, compound 3 obtained in step (3) was added and the reaction was continued for 1-2 h to obtain silica sol.

6. The heat-curable high-temperature resistant electronic paste according to claim 5, characterized in that: The mass ratio of compound 1 to vinyltriethoxysilane in step (2) is (0.4-0.7):

1.

7. The heat-curable high-temperature resistant electronic paste according to claim 5, characterized in that: The mass ratio of tetraethyl orthosilicate to compound 3 in step (4) is 1:(0.1-0.4).

8. The heat-curable high-temperature resistant electronic paste according to claim 1, characterized in that: The chain extender is a low-viscosity linear hydroxy silicone oil.

9. The heat-curable high-temperature resistant electronic paste according to claim 1, characterized in that: The filler is a composition of a conductive filler and a reinforcing filler.

10. A method for preparing the heat-curable high-temperature resistant electronic paste according to any one of claims 1 to 9, characterized in that: The following steps are involved: S1. Add silane A, silane B, silane C, and solvent A to the first reaction kettle and stir at 50-60° C. for 5-10 minutes to obtain solution A; S2. Add the pH regulator and silica sol into the second reaction kettle and stir for 5-10 minutes to obtain solution B; S3, adding glass powder, filler and part of solvent B into a grinder, and grinding until the average particle size is less than 40 μm to obtain slurry A; S4. Add solution A obtained in step S1 to solution B obtained in step S2, heat the mixture to 30-50° C. and react for 2-3 hours. Then heat the mixture to 70-75° C. and distill the mixture at an absolute pressure of 280-320 mbar for 2.5-3.5 hours. Then, add the remaining solvent B and chain extender, continue heating the mixture to 80-90° C. and distill the mixture at an absolute pressure of 480-520 mbar for 1-2 hours. Then, add slurry A obtained in step S3, and continue stirring for 10-20 minutes to obtain a thermosetting high-temperature resistant electronic paste.